2013
DOI: 10.4161/rna.24370
|View full text |Cite
|
Sign up to set email alerts
|

miR-200b targets GATA-4 during cell growth and differentiation

Abstract: GATA-4 is an important transcription factor involved in several developmental processes of the heart, such as cardiac myocyte proliferation, differentiation and survival. The precise mechanisms underlying the regulation of GATA-4 remain unclear, this is especially true for the mechanisms that mediate the post-transcriptional regulation of GATA-4. Here, we demonstrate that miR-200b, a member of the miR-200 family, is a critical regulator of GATA-4. Overexpression of miR-200b leads to the downregulation of GATA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…More recently, Yao et al demonstrated that miR-200b was a critical regulator of the zinc finger transcription factor GATA-4, which regulates the expression of CCND1 at the transcriptional level. Their results supported that miR-200b could regulate tumor cell growth and differentiation by targeting GATA-4 to downregulate the expression of CCND1 [77]. Thus, these findings support that miR-200 can exert control over the cell cycle at many levels through the modulation of several different factors.…”
Section: Tumor Suppressive Signatures Of Mir-200mentioning
confidence: 63%
“…More recently, Yao et al demonstrated that miR-200b was a critical regulator of the zinc finger transcription factor GATA-4, which regulates the expression of CCND1 at the transcriptional level. Their results supported that miR-200b could regulate tumor cell growth and differentiation by targeting GATA-4 to downregulate the expression of CCND1 [77]. Thus, these findings support that miR-200 can exert control over the cell cycle at many levels through the modulation of several different factors.…”
Section: Tumor Suppressive Signatures Of Mir-200mentioning
confidence: 63%
“…Recent reports indicated that miRNA-200b is highly correlated with cell proliferation222425. Especially, in cardiac cell lines, Yao et al 31. demonstrated that miR-200b overexpression inhibited the cell growth and downregulated the expression of cyclin D1 and myosin heavy chain (MHC) by regulating the expression of GATA-4.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR99a attenuated Nodal signaling via repression of Smarca5 chromatin remodeling activity and cardiac gene promoters were shown to have increased H3K27me3 levels. A variety of additional studies have functionally confirmed miRNA roles in pluripotent-CM differentiation including miR199a-3p, miR590-3p (91), miR363 (Gupta and Rao, 2014), miR499 miR200b (Yao et al, 2013), miR1, miR499 (Fu et al, 2011), andmiR-133 (Takaya et al, 2009). However, additional work will be needed to determine ncRNA control of and regulation by, other epigenetic regulators of chromatin architecture through CM differentiation.…”
Section: Epigenetics Of Pluripotent-cm Differentiationmentioning
confidence: 93%